Cognitive impairment is correlated with reduced quality of life in patients with clinically isolated syndrome - Carolina Fiorin Anhoque; Laurentino Biccas-Neto; Simone Cristina A. Domingues; Antônio Lúcio Teixeira; Renan Barros Domingues (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To evaluate the quality of life (QoL) and potential QoL determinants in patients with clinically isolated syndrome (CIS). METHODS: Eighteen CIS patients and eighteen controls were submitted to QoL evaluation with Functional Assessment of Multiple Sclerosis QoL instrument (FAMS). Cognition was evaluated with specific battery tests; Anxiety and depression with Beck Anxiety (BAI) and Depression (BDI) Inventories and Neurological disability with Guy's Neurological Disability Scale (GNDS). RESULTS: There was a significant difference in QoL between CIS patients and controls. CIS patients had worse performance in Paced Auditory Serial Addition 2 seconds (p=0.009) and fluency tests (p=0.0038). There was a significant difference in BAI (p=0.003), but no significant difference in BDI between patients and controls. There were significant correlations between QoL measure and verbal fluency and Stroop's test. CONCLUSIONS: Cognition, but not anxiety, depression and disability, was associated with reduced quality of life.